Marianne at the Beach: The French Burkini Controversy and the Shifting Meanings of Republican Secularism. (2nd January 2018) - Almeida, Dimitri
ABSTRACT: This paper critically examines the controversy surrounding2 burkini-style swimsuits that arose in summer 2016 in France. Through a comparative analysis of representations of the 'burkini' in political discourse and in Muslim online forums, I explore the contested meanings attached to full-body 'Islamic' swimsuits. Contrary to hegemonic French representations of 'Islamic' swimsuits as manifestations of a politicised religiosity, 'burkinis' are described by women who wear them as an opportunity to claim access to spaces of leisure while still obeying their belief in dressing modestly. The burkini bans, I argue, have contributed to weakening expressions of religiosity that seek to resolve tensions between religious belief and a secular understanding of leisure and sociability. Elaborating on the transformations of French republicanism, I explore how the burkini controversy is related to the rise of exclusionary conceptions of secularism.